2007
DOI: 10.1007/s12070-007-0107-1
|View full text |Cite
|
Sign up to set email alerts
|

Papillary carcinoma of thyroglossal cyst

Abstract: Malignancy of thyroglossal cyst is a rare entity. Medical literature has reported only a very few cases till date. Histopathologically papillary carcinoma of thyroglossal cyst is the most common variety encountered in clinical practice. Surgical excision by Sistrunk operation is the standard treatment of choice followed by subtotal or total thyroidectomy whenever indicated. We report here two cases of thyroglossal cyst carcinomas and their respective management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Ninety‐eight articles met the inclusion criteria and were included in the final analysis with a total population of 164 patients. Eighty‐one case reports and 17 case series were included 4–101 . The largest case series included 18 patients, and the studies that we evaluated spanned from 1986 to 2016.…”
Section: Resultsmentioning
confidence: 99%
“…Ninety‐eight articles met the inclusion criteria and were included in the final analysis with a total population of 164 patients. Eighty‐one case reports and 17 case series were included 4–101 . The largest case series included 18 patients, and the studies that we evaluated spanned from 1986 to 2016.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence has confirmed that the dysregulation of the MMPs/TIMPs signaling pathway was closely correlated to fibrosis and inflammation. [ 24,25 ] As described in Figure 3A, compared with the control group, the protein levels of MMPs, including MMP‐1, MMP‐2, MMP‐3, MMP‐9, MMP‐13, and MMP‐19 in BEAS‐2B cells were generally increased after CSE treatment. However, the increased MMPs were further decreased in different degrees by PPI treatment, especially on MMP‐9 expression.…”
Section: Resultsmentioning
confidence: 96%